2020
DOI: 10.3390/ijms21218102
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment of Primitive and Metastatic Breast Cancer: Implications for Novel Therapeutic Strategies

Abstract: Breast cancer evolves thanks to a dense and close interaction with the surrounding tumor microenvironment (TME). Fibroblasts, leukocytes, blood and lymphatic endothelial cells and extracellular matrix are the constituents of this entity, and they synergistically play a pivotal role in all of the stages of breast cancer development, from its onset to its metastatic spread. Moreover, it has been widely demonstrated that variations to the TME can correspond to prognosis variations. Breast cancer not only modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 162 publications
0
27
0
1
Order By: Relevance
“…The TME comprises stromal cells, bioactive molecules secreted by tumors and stromal cells, the extracellular matrix (ECM), and the lymphatic and vascular systems, all of which play key roles in tumorigenesis and metastasis (Wu and Dai, 2017). TME has been recently widely associated with the prognosis of many cancers and lymph and distant metastasis, including in breast cancer (Zarrilli et al, 2020). A study has found that a variety of transcription factors in the microenvironment induce high expression of microRNA-10b (miR-10b) in metastatic breast cancer cells, promoting cancer cell migration, invasion, and metastasis (Ma et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The TME comprises stromal cells, bioactive molecules secreted by tumors and stromal cells, the extracellular matrix (ECM), and the lymphatic and vascular systems, all of which play key roles in tumorigenesis and metastasis (Wu and Dai, 2017). TME has been recently widely associated with the prognosis of many cancers and lymph and distant metastasis, including in breast cancer (Zarrilli et al, 2020). A study has found that a variety of transcription factors in the microenvironment induce high expression of microRNA-10b (miR-10b) in metastatic breast cancer cells, promoting cancer cell migration, invasion, and metastasis (Ma et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HIF-1α-dependent hypoxia can increase macrophage-mediated T cell suppression. In a hypoxic breast cancer model, myeloid HIF-1α was shown to mediate the induction of T cell suppression by the control of arginase-I (ArgI) and inducible NO synthase (iNOS) in macrophages [63]. Hypoxic macrophages directly upregulate angiogenic molecules such as angiopoietin, VEGF, VEGFR, FGF2, IL-8, and CXCL8 to promote angiogenesis.…”
Section: Hypoxia Attracts and Retains Tumor-associated Macrophagesmentioning
confidence: 99%
“…The BC cells are surrounded by different stromal components that have an important role in the BC’s development, in its metastatic ability and its response to therapy [ 24 ]. A tumor is much more than clusters of transformed cells standing alone, and the epithelial tumor cells can only develop in an aberrant microenvironment composed of altered extracellular matrix and several non-transformed cells, such as cancer-associated fibroblasts (CAF), adipocytes, endothelial cells, extracellular matrix components, blood vessels and immune cells, all of which compose the tumor microenvironment (TME) [ 16 , 24 , 25 ].…”
Section: Breast Cancer Microenvironmentmentioning
confidence: 99%
“…TME stromal components have different functions and interactions in BC, wherein tumor development can influence the microenvironment, which provide an important support for BC development [ 16 , 25 , 26 ]. The stromal constituent has an abundance of inflammatory cells and activated fibroblasts expressing extracellular matrix (ECM) components, as well as growth factors that promote the survival and proliferation of tumor cells [ 27 ].…”
Section: Breast Cancer Microenvironmentmentioning
confidence: 99%